(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: A partial rupture is likely secondary to the fact that the two bundles of the ACL have a synergistic yet distinctly different biomechanical function at different knee flexion angles. Recent interest focused on establishing pre and intraoperative ways of assessing the different types of symptomatic one bundle tears in order to perform an individual ACL augmentation. Treatment of partial ACL tears depends entirely on making an accurate diagnosis and determining degree of impairment. For some patients with partial tears, little morbidity is associated with the injury, and knee stability may be adequate for participation in sports and for all activities of daily living. Treatment in this scenario is largely supportive recommending that the patient take the time to recover from the initial injury and, after rehabilitation, to make a gradual return to sport. Operative intervention is needed in other cases, but such a decision should be taken while considering various factors, this includes: age, activity level, degree of laxity on physical examination, associated injuries, and symptomatic instability. Most clinicians would agree that symptomatic and debilitating instability require a more aggressive approach, likely in the form of operative intervention. The ACL augmentation is performed similar to a (traditional) single bundle technique while sparing the intact ACL fibers. This may support mechanical strength of the reconstruction, especially in the early postoperative period, and may maintain mechanoreceptors, neural elements and blood vessels to allow better proprioception, vascularization and an accelerated rehabilitation with faster return to sports. The aim of this study was to evaluate the results of arthroscopic reconstruction of partial ACL tears. Objectives: This work aims to evaluate the results of arthroscopic reconstruction of partial ACL tears. Materials and Methods: Twenty five patients with an ACL partial tear were included at this study; anatomic single bundle augmentation using the semi-tendinosus and gracilis auto-grafts was done. All cases (100%) were males. Of the knees involved, 15 were right (60%) and 10(40%) were left. Age ranges from 17 to 40 years and the mean age was 30.28± 5.38 years and the average time between the injury and the surgical interference was 4.6± 3.97 months. Affected bundle among patients was PL in 18 patients (72%) and 7 patients (28%) with affected AM bundle. Follow up on regular basis after reconstruction was done for two years postoperatively. Assessment was done before surgery and at the end of follow up using IKDC objective score , lysholm score,Tegner activity level scale and post operative KT -1000 measurements. Results: The overall results of the present study, as measured by the IKDC evaluation system after 24 months follow up, were 11 patients out of 25 patients (44%) had score A and 14 patients out of 25 patients (56%) had score B. The Lysholm score improved from a mean 63.08 ± 9.92 (before surgery) to 92.60 ± 3.88 at the end of follow up.Measurements by Tegner activity level scale (mean activity level before surgery was 5.1± 0.9,mean current activity level was 2.0 ± 0.9 and mean activity level after surgery improved to 5.1± 0.9 ).Measurements by postoperative K.T 1000 and evaluate the diff. between normal and injured knee after 24 months follow up, were 4 patients out of 25 patients (16%) were 1 m.m. diff. , 10 patients out of 25 patients (40%) were 2 m.m. diff. and 11 patients out of 25 patients were 3 m.m. diff.). Conclusion: Diagnosis of symptomatic AM or PL bundle tear is a combination of the patient’s history and complaints, clinical examination, MRI, and arthroscopic evaluation. Good results have been achieved with preserving the remanants of the torn ACL and performing augmentation but reliable diagnosis of partial torn ACL and assessing the vaidity of the remanants to be kept and decision to do an augmentation procedure has to be taken after arthroscopic assessment.